2021
DOI: 10.3389/fgwh.2021.656062
|View full text |Cite
|
Sign up to set email alerts
|

Women Deprivation Index and Family Planning Utilisation in Urban Geography of West African Countries

Abstract: Inequalities in health care utilisation and outcomes vary significantly across geographies. Though available evidence suggests disparity in contraceptive uptake in favour of urban compared with rural geographies, there are unassessed nuances among women in urban communities. This study examines some of these disparities within the context of socioeconomic deprivations and family planning utilisation among urban women in West Africa. A secondary analysis of the most recent Demographic and Health Survey dataset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, there are unassessed disparities and nuances in urban settings. Urban geographies in many developing countries, especially in Nigeria, are susceptible to alarming crime rates, poverty, high cost of living, environmental hazards and socioeconomic inequalities [15][16][17]. Poverty in the urban setting is linked to the worsening environmental degradation and poor socioeconomic infrastructure coupled with poor governance and institutional deficiencies [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are unassessed disparities and nuances in urban settings. Urban geographies in many developing countries, especially in Nigeria, are susceptible to alarming crime rates, poverty, high cost of living, environmental hazards and socioeconomic inequalities [15][16][17]. Poverty in the urban setting is linked to the worsening environmental degradation and poor socioeconomic infrastructure coupled with poor governance and institutional deficiencies [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, evidence from studies done in Sub Saharan Africa, western Africa, D.R Congo and Nigeria reported that urban women use modern contraception more frequently than rural women (1,15,16), and rural fertility is significantly higher than urban fertility (1).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Sierra Leone using the 2013 demographic health survey (DHS) data found that living in an urban area was associated with increased odds of modern contraceptive utilization among married or in-union women when compared to living in rural areas (14). Additionally, evidence from studies done in Sub Saharan Africa, western Africa, D.R Congo and Nigeria reported that urban women use modern contraception more frequently than rural women (1, 15, 16), and rural fertility is significantly higher than urban fertility (1).…”
Section: Introductionmentioning
confidence: 99%